Pragmatic speech and language therapy in the Bangladeshi context for children with hearing impairment - Mobasshera Islam (Journal of Child Language Acquisition and Development)
Speech and Language Therapy (SLT) is crucial for children with hearing impairment (CHI) to develop speech and language skills. Researchers globally have explored different methods to enhance SLT effectiveness for CHI. This study aimed to identify gaps between parents' and therapists' perspectives on implementing pragmatic therapy  to uncover barriers to effective therapy for CHI in Bangladesh. Understanding these gaps and barriers sheds light on the current state of SLT for CHI in Bangladesh. Addressing these issues can improve SLT quality and accountability, and raise awareness among therapists and authorities about pragmatic SLT for CHI in Bangladesh. The study involved Speech and Language Therapists (SALT) and parents of hearing-impaired children. Data was gathered through semi-structured questionnaires from 12 SALT and 24 parents whose children received therapy for at least a year. Qualitative analysis of their experiences, research, and observations revealed obstacles affecting SLT effectiveness for Bengali-speaking CHI in Bangladesh. While some factors identified in literature were implemented by therapists, others faced barriers due to negligence or contextual challenges. Overcoming these barriers could enhance the pragmatic features of SLT for Bengali-speaking CHI. Addressing these findings could significantly improve SLT quality, benefiting language acquisition and speech development for HI children in Bangladesh, and positively impacting their overall life. Thus, this research contributes to enhancing SLT quality for Bengali-speaking HI children in Bangladesh.